Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Tenaga Kontrak Kerja (TKK) di Sekolah Menengah Pertama Negeri 21 Kota Bekasi - Luciana Cecilia Situmorang; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to examine how remuneration and work discipline impact the performance of contract workers (TKK) at Junior High School 21 in Bekasi City. There were sixty participants in this study. This study adopts a quantitative methodology and uses a questionnaire to collect data. Multiple linear regression analysis is performed as the method of data analysis. The findings of this study indicate that compensation has no significant effect on performance. Discipline in the workplace influences productivity. Pay and work discipline have a substantial impact on the performance of contract employees at Junior High School 21 in Bekasi City.